Stock Market Volatility in ASEAN Plus Three Countries during Geopolitical Crisis - Fatikasari, Imania; Robiyanto, Robiyanto; Wijayanto, Petrus (Jurnal Riset Akuntansi dan Keuangan, 2024)
The purpose of this study is to examine the effect of stock market volatility in ASEAN Plus Three Economic Relation toward gold prices and the value of the US Dollar Index during geopolitical crisis. The technique used in this study is Generalized Autoregressive Conditional Heteroskedasticity (GARCH) or GARCH. This study found that the volatility of PSEi, STI, and KOSPI effect the gold price positively. The same finding also applies on the US Dollar Index, where the volatility of the VN30 and KOSPI proved to have a positive effect. Therefore, that increased stock market volatility encourages investors to seek alternative investments such as Gold and the US Dollar Index.